Cooperative blood-feeding and the function and implications of feeding aggregations in the sand fly, Lutzomyia longipalpis (Diptera: Psychodidae). - Frédéric Tripet; Simon Clegg; Dia-Eldin Elnaiem; Richard D Ward (Public Library of Science (PLoS), 2009)
Given the importance that the evolution of cooperation bears in evolutionary biology and the social sciences, extensive theoretical work has focused on identifying conditions that promote cooperation among individuals. In insects, cooperative or altruistic interactions typically occur amongst social insects and are thus explained by kin selection. Here we provide evidence that in Lutzomia longipalpis, a small biting fly and an important vector of leishmaniasis in the New World, cooperative blood-feeding in groups of non-kin individuals results in a strong decrease in saliva expenditure. Feeding in groups also strongly affected the time taken to initiate a bloodmeal and its duration and ultimately resulted in greater fecundity. The benefits of feeding aggregations were particularly strong when flies fed on older hosts pre-exposed to sand fly bites, suggesting that flies feeding in groups may be better able to overcome their stronger immune response. These results demonstrate that, in L. longipalpis, feeding cooperatively maximizes the effects of salivary components injected into hosts to facilitate blood intake and to counteract the host immune defences. As a result, cooperating sand flies enjoy enormous fitness gains. This constitutes, to our knowledge, the first functional explanation for feeding aggregations in this species and potentially in other hematophagous insects and a rare example of cooperation amongst individuals of a non-social insects species. The evolution of cooperative group feeding in sand flies may have important implications for the epidemiology of leishmaniasis.